Posições e disposições na trajetória de Francisco Weffort (1937-1994) - Caldara, Marcus Vinicius Calderan (2024)
This dissertation examines the trajectory of the political scientist Francisco Correa Weffort. His academic journey, intellectual output, and political career are frequently of interest to researchers in the field of political thought in Brazil. Working in institutions that were central to the development of social sciences in the country, Weffort became a reference in studies on populism in Brazilian and Latin American politics; about the nationaldevelopmentalist ideology; about the history of the trade union movement; and about the consolidation of the democratic regime in Brazil. Furthermore, his role as a public figure, as founder and general secretary of the Workers' Party (PT) and later as Minister of Culture in the Fernando Henrique Cardoso government, of the Brazilian Social Democracy Party (PSDB), is also a frequent object of interest among researchers. The literature on the topic tends to emphasize exclusively the evolution of ideas as an explanatory element of Weffort's trajectory. This work seeks to adopt an approach opposite to this trend, exploring the explanatory links between his objective shifts in position in the social space and his position taking in the political sphere